SYNTHESIS, CHARACTERIZATION, EVALUATION OF ANTIMICROBIAL PROPERTIES AND QUANTUM CHEMICAL CALCULATIONS OF 3, 4- DIHYDROPYRIMIDIN-2(1,H)-ONES - T.K.SHABEER; A.SUBRAMANI (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this study was to synthesize substituted 3,4-dihydropyrimidin-2(1H)-ones (DHP) and to evaluate them for their antibacterial and antifungal activities. These compounds were synthesized by cyclocondensation reaction between substituted aromatic aldehyde i.e.,p-anisaldehyde, active methylene compounds (ethyl acetoacetate/acetylacetone), urea in the presence of CuCl2.2H2O and few drops of Con.HCl by grindstone technique. The products are obtained in good yield under mild, solvent free and ecofriendly conditions. The structures of these compounds have been confirmed on the basis of their IR and NMR spectral data. The structural parameters like bond distances and bond angles for the optimized structures of the compounds were evaluated by abinitio Hartree-Folk level and B3CYP methods using the basis sets 6-31h(d,p) and CC-PUDZ to determine the exact geometry of the synthesized compound. The dihydropyrimidinone derivatives synthesized have been tested for antibacterial activity against Micrococcus luteus, Escherichia coli & Pseudomonas aeruginosa, and for antifungal activity against Aspergillus niger, Candida albicans & Candida kefyr.